Menentukan Prioritas Penanganan Ruas Jalan Nasional di Pulau Bangka - Benardus Munthe, Raymond; Hario Setiadji, Bagus; Darsono, Suseno (MEDIA KOMUNIKASI TEKNIK SIPIL, 2015)
National road are crucial to the economy and it spurs the economic development potential of the area contained in the province of Bangka Belitung Archipelago. National road lines is the busiest traffic lane linking inter-cities/regencies in Bangka Island requires maximum handling but the ability of the central government in providing funding is very limited. Prioritization of road handling must be done evenly as needed so that the purpose of the existence of these roads remains unfulfilled. The purpose of this study was to determine the priority handling of national road Lines in Bangka Island by the method of Analytical Hierarchy Process (AHP) using 6 (six) criteria. Data results of the questionnaire showed that of 6 (six) criteria taken in this study namely accessibility (19.3%) is the most dominant criteria. Followed mobility (17.6%), the condition of roads (17.1%), current road segment (16.3%), the development of regional (15.9%), and Economic of Gross Regional Domestic Product (13.8%). By entering the 6 (six) criteria to 21 segments, the roads segment that became the priority of road handling is Sungailiat – Boundary of Pangkalpinang  followed Tanjung Gudang - Lumut, and the next successive.